Quem liga para o psiquismo na escola médica?A experiência da Liga de Saúde Mental da FMB - Unesp - Gonçalves, Rebeca Jesumary [UNESP]; Ferreira, Esther Angélica Luiz [UNESP]; Gonçalves, Graziella Galvão [UNESP]; Lima, Maria Cristina Pereira [UNESP]; Ramos-cerqueira, Ana Teresa De Abreu [UNESP]; Kerr-correa, Florence [UNESP]; Smaira, Sumaia Inaty [UNESP]; Torres, Albina Rodrigues [UNESP] (Associação Brasileira de Educação Médica, 2009)
Considering the importance of mental health for general health practice, there has been an increasing demand by medical students for better training in this area. The main aim of the present article is to describe the experience of the Students' League on Mental Health (LISM) at the Botucatu Medical School, São Paulo State University (UNESP), in teaching mental health contents as extracurricular activities. The article describes the initial difficulties in the league's organization, as well as its structure and functioning and the main activities developed by the students since it was founded in 2004. The LISM has been successful in complementing medical training in this area, since it encompasses preventive and health promotion activities, including those targeting the students' own mental health. Some concerns regarding the role of students' leagues in mental health in medical schools are also discussed, including the risks of favoring early specialization in psychiatry, fueling the false dichotomy between physical and mental health, and simply reproducing regular curricular activities. These leagues should not discourage the academic community from struggling to value, integrate, and systematically include mental health themes in the official curriculum, which are indispensable to proper training of general practitioners.

A importância da saúde mental nas práticas em saúde fez surgir nas escolas médicas a demanda por uma capacitação aprimorada dos graduandos nessa área. Este artigo tem como principal objetivo descrever a experiência da Liga Acadêmica de Saúde Mental (LISM) da Faculdade de Medicina de Botucatu - Unesp como atividade de ensino extracurricular. Relatam-se sua formação, objetivos, dificuldades iniciais, composição, modo de funcionamento e principais atividades desenvolvidas desde 2004. Acredita-se que a LISM tem tido êxito em complementar a formação médica nessa área, pois atua na prevenção e promoção da saúde, incluindo atividades voltadas à saúde mental dos estudantes. Discute-se também criticamente a atuação das Ligas de Saúde Mental nas escolas médicas, incluindo alguns riscos, como o de favorecer a especialização precoce em Psiquiatria, de aumentar a falsa dicotomia entre saúde física e mental ou simplesmente reproduzir atividades acadêmicas oficiais. Tais atividades extracurriculares não devem desmobilizar a comunidade acadêmica na luta pela valorização, integração e inserção sistemática e longitudinal de temas de saúde mental no currículo oficial dos cursos de graduação, indispensáveis à adequada formação dos médicos generalistas.
Who cares about the psyche in medical school? The experience with the Mental Health League at the school of medicine, State University of São Paulo, Brazil
Keywords: Medical education; Mental health; Psychiatric disorders; Academic leagues; Ensino médico; Saúde mental; Transtornos psiquiátricos; Ligas acadêmicas